Pembuatan Bioetanol Dari Pati Umbi Talas (Colocasia esculenta [L] Schott) Melalui Hidrolisis Asam dan Fermentasi - Sadimo, Mariskian M.; Said, Irwan; Mustapa, Kasmudin (Jurnal Akademika Kimia, 2016)
Taro plant contains high enough of carbohydrate, so it can be used as an alternative raw material for producing bioethanol. This study aimed to determine the ratio of hydrochloric acid to taro root starch and hydrolysis time of taro root starch for producing a high sugar content, as well as to determine the bioethanol content produced from the fermentation of taro root starch using baker’s yeast. The results showed that the best ratio of hydrochloric acid 15% to the taro root starch was at 10:1 (v/w), resulted in a total sugar content of 0.651%. The best hydrolysis time of taro root starch was 2.5 hours, resulted in sugar content of 0.653%. The fermentation of sugar resulted in from hydrolysis was carried out at room temperature for 5 days. The ethanol content obtained from the fermentation was 7.716%.